2005
DOI: 10.1152/ajpregu.00200.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic pulmonary vasoconstriction in reptiles: a comparative study of four species with different lung structures and pulmonary blood pressures

Abstract: Low O2 levels in the lungs of birds and mammals cause constriction of the pulmonary vasculature that elevates resistance to pulmonary blood flow and increases pulmonary blood pressure. This hypoxic pulmonary vasoconstriction (HPV) diverts pulmonary blood flow from poorly ventilated and hypoxic areas of the lung to more well-ventilated parts and is considered important for the local matching of ventilation to blood perfusion. In the present study, the effects of acute hypoxia on pulmonary and systemic blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
4
22
0
1
Order By: Relevance
“…This suggests that muscarinic ACh receptors are involved in hypoxia chemoreception and, by extension, that ACh is an important neurotransmitter in the initiation of the cardiovascular response to hypoxemia. These results are supported by previous studies on turtles and rattlesnakes, which found that injection of atropine eliminated the tachycardia normally seen during hypoxia exposure (Comeau and Hicks, 1994;Skovgaard et al, 2005). Injection of methysergide also blocked the effect of NaCN on f H (Fig.…”
Section: Cardiovascular Variablessupporting
confidence: 86%
See 4 more Smart Citations
“…This suggests that muscarinic ACh receptors are involved in hypoxia chemoreception and, by extension, that ACh is an important neurotransmitter in the initiation of the cardiovascular response to hypoxemia. These results are supported by previous studies on turtles and rattlesnakes, which found that injection of atropine eliminated the tachycardia normally seen during hypoxia exposure (Comeau and Hicks, 1994;Skovgaard et al, 2005). Injection of methysergide also blocked the effect of NaCN on f H (Fig.…”
Section: Cardiovascular Variablessupporting
confidence: 86%
“…amphibians, birds and mammals) (Heistad and Abboud, 1980;Faraci, 1986;Kruhoffer et al, 1987;van Klaveren and Demedts, 1998;Andersen et al, 2003), stimulation of putative carotid artery chemoreceptors in lizards produced an increase in f H and f R while keeping MAP constant. The physical association of chemoreceptive cells in the carotid artery of the tegu, however, differed from the general pattern seen in most other terrestrial taxa.…”
Section: Evolution Of Carotid Chemoreceptionmentioning
confidence: 99%
See 3 more Smart Citations